Indicators of transport logistics of locomotives of diesel traction on Kattakurgan-Navoi section in operation - Ablyalimov Oleg (E3S Web of Conferences, 2023)
The subject of these studies is the assessment of the fuel and energy efficiency of using locomotives of diesel traction in various conditions for organizing the operational activities of railways with the third type of track profile. The purpose of the study: to substantiate the logistic parameters of the main indicators of the transport logistics of freight trains and the transportation work of three-section main (train) freight diesel locomotives of the 3TE10M series on the real hilly-mountainous section of Kattakurgan - Navoi of the railway line of the Samarkand - Navoi - Bukhara of the Uzbek railway. Research criterion: the value of the kinematic parameters of the movement of freight trains and the parameters of the main indicators of the energy efficiency of the studied diesel locomotives of the 3TE10M series in quantitative and monetary terms. The author obtained various trajectories of the speed and time of the train, tables, and graphs of logistic kinematic parameters for two types of movement of a freight train with different masses of trains and parameters of the main indicators of the energy efficiency of the studied diesel locomotive for three options for traction calculation on the hilly-mountainous section of Kattakurgan - Navoi of the Uzbek Railway roads. Also, the author compiled the corresponding regression equations for calculating the values of the mentioned logistic parameters, taking into account the dynamics of change and the rate of increase or decrease in the accepted range of fluctuations in the mass of freight trains, and set differentiated standards of consumption of full-scale diesel fuel for each stop of the freight train. The results of the study can be used by specialists in the operation shop of the Bukhara locomotive depot to develop diesel fuel consumption standards for diesel locomotives of the 3TE10M series and substantiate the traction quality of the track profile on the hilly-mountainous railway direction Samarkand - Navoi - Bukhara of the Uzbek railway.